PROSEDUR AUDIT ATAS UTANG USAHA PADA PT XYZ OLEH KANTOR AKUNTAN PUBLIK PKF HADIWINATA - Nur Aninda Rizki, (2022)
The purpose of writing this final report is to find out the accounts payable of PT XYZ which has been audited by the PKF Hadiwinata Public Accounting Firm. Accounts payable is a fairly important account in the financial statements, and to report that accounts payable have been properly filed. The auditor also conducts an audit program based on the provisions of the PKF Hadiwinata Public Accounting Firm. Trade payables arise because of the purchase of equipment on credit to support the company's operations, and the results of the accounts payable audit procedures that the author did at PT XYZ were not found to be misstatements so that they were reasonable in all material respects and in accordance with accounting standards applicable in Indonesia.